The impact of oxytocin and GlyT1 inhibitors on social behaviour - Kohli, Shivali (2018)
Schizophrenia is a complex mental disorder characterised by various symptoms which fall into three categories of positive, negative and cognitive. In particular, negative symptoms are poorly treated by current medications although several adjunctive therapies are under investigation including Glycine Transporter (GlyT1) inhibitors and neuropeptides such as oxytocin. Despite accumulating preclinical and clinical evidence that such compounds can influence social behaviour and improve negative symptoms in patients, there is little information as to the precise mechanisms by which they work. Therefore, the aims of this thesis were to ultimately determine some of the key regions and potential signalling pathways activated following administration of these compounds in Lister-hooded rats.